THE EFFECT OF TOTAL PHYSICAL RESPONSE AND SUGGESTOPODIA METHODS ON VOCABULARY MASTERY - Karokaro, Indahsari (MEDIA UNIKA - Majalah Ilmiah, 2013)
The objectives of this study are to investigate the effect of Total Physical Response and Suggestopedia Methods on Vocabulary Mastery and to find out which of these methods is the most significantly effective. Experiment of design was carried out to achieve the objective. Ninety students of the first year students of State Junior High School of Medan 1 in the 2004/2005 academic years taken as the sample of this study in clustering sampling with 90 students divided into three groups ( two groups as experimental and a group as a control. First, the researcher administered a pre-test for three groups, then the first experimental group is treated by using total physical response method, the second experimental group is treated by using suggestopedia method; and the third group is not given any treatment, and at the last, the researcher registered a post-test for the three groups. The data was analyzed by applying one way ANOVA.The result of testing the first hypothesis showed that the Fobserved is greater than the Ftable (7.895> 3. 94 (df: 0.01)). When on the Newman-Keuls formula was applied to find which of the three methods is the most effective method, because the means of the scores is the highest, follows by the second experimental method. In statistic, the writer would say that the total physical response and suggestopedia methods significantly effected on vocabulary mastery.